2001
DOI: 10.2310/6650.2001.34045
|View full text |Cite
|
Sign up to set email alerts
|

New Technique for Gene Transfection Using Laser Irradiation

Abstract: This method enables us to transfect targeted cells, ie, cells in suspension as well as attached cells, with a simple technique that does not involve harmful vectors. The present method is very useful for gene transfection in cellular biotechnology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 19 publications
0
29
1
Order By: Relevance
“…It has been previously shown that the transfection efficiency decreases significantly when transfected with a plasmid concentration less than 10 mg/ml [3,15]. However we show that, in the presence of Nupherin-neuron, we could lower the plasmid concentration to 3.3 mg/ml without compromising the resulting transfection efficiency.…”
Section: Biophotonicscontrasting
confidence: 55%
“…It has been previously shown that the transfection efficiency decreases significantly when transfected with a plasmid concentration less than 10 mg/ml [3,15]. However we show that, in the presence of Nupherin-neuron, we could lower the plasmid concentration to 3.3 mg/ml without compromising the resulting transfection efficiency.…”
Section: Biophotonicscontrasting
confidence: 55%
“…Other studies of laser-induced gene delivery were carried out on single cells. [8][9][10][11] Our results, that laser engery is capable of enhancing gene transfer as well in cell suspensions, are promising for future in vivo laser application in the prostate. James et al 14 considered that direct in vivo gene transfer to urological organs is possible by physical methods like electroporation.…”
Section: Discussionmentioning
confidence: 64%
“…They also noted that the permeability of the cell membrane is modified at the site of the beam impact. Shirahata et al 10 observed a similar effect of gene transfer when a pulse laser irradiation was focused on a cell membrane. All the above studies show that the cells upon laser irradiation undergo a change in the permeability of the plasma membrane or form pores in the membrane at the site of contact.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Optical cell translocation satisfies these criteria. A variety of lasers, ranging from continuous wave visible sources [4][5][6][7][8] to pulsed infrared [9][10][11][12] sources, have been applied for efficient introduction of biomaterials into mammalian cells.…”
Section: Introductionmentioning
confidence: 99%